Solutions of k-Hypergeometric Differential Equations. (30th April 2014) - Mubeen, Shahid; Naz, Mammona; Rehman, Abdur; Rahman, Gauhar
Abstract : We solve the second-order linear differential equation called the k -hypergeometric differential equation by using Frobenius method around all its regular singularities. At each singularity, we find 8 solutions corresponding to the different cases for parameters and modified our solutions accordingly.